2020
DOI: 10.1098/rstb.2019.0602
|View full text |Cite
|
Sign up to set email alerts
|

Compartmentalization drives the evolution of symbiotic cooperation

Abstract: Across the tree of life, hosts have evolved mechanisms to control and mediate interactions with symbiotic partners. We suggest that the evolution of physical structures that allow hosts to spatially separate symbionts, termed compartmentalization, is a common mechanism used by hosts. Such compartmentalization allows hosts to: (i) isolate symbionts and control their reproduction; (ii) reward cooperative symbionts and punish or stop interactions with non-cooperative symbionts; and (iii) reduce direct conflict am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
76
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(77 citation statements)
references
References 156 publications
1
76
0
Order By: Relevance
“…T. endolucinida both had the additional potential to utilize methanol as a source of energy and carbon with an xox-type methanol dehydrogenase and the serine pathway for C1-carbon incorporation into biomass. Compartmentalizing coexisting symbiont species into separate bacteriocytes could prevent direct competition by allowing the host to partition resources and discriminate cooperative symbionts from potential cheaters that might destabilize the symbiosis (45). Consistent with this, our FISH analyses showed that although symbiont species cooccurred in host individuals they never cooccurred in single host bacteriocytes (Fig.…”
Section: Discussionsupporting
confidence: 79%
“…T. endolucinida both had the additional potential to utilize methanol as a source of energy and carbon with an xox-type methanol dehydrogenase and the serine pathway for C1-carbon incorporation into biomass. Compartmentalizing coexisting symbiont species into separate bacteriocytes could prevent direct competition by allowing the host to partition resources and discriminate cooperative symbionts from potential cheaters that might destabilize the symbiosis (45). Consistent with this, our FISH analyses showed that although symbiont species cooccurred in host individuals they never cooccurred in single host bacteriocytes (Fig.…”
Section: Discussionsupporting
confidence: 79%
“…The selection of a particular species or population in a segment of a gradient immediately influences the gradient itself (for instance consuming O 2 , or lowering the pH), or create new associated gradients, as gradients of nutrients, inhibitory substances, quorum-sensing molecules, or pheromones, contributing to the fluidity of the multidimensional niche landscape, and the intensity of biotic interactions. That facilitate genetic exchanges with neighboring kin populations sharing the same selective compartment, increasing the evolvability of the lineage ( Chomicki et al, 2020 ).…”
Section: Niches Gradients and Bacterial Diversificationmentioning
confidence: 99%
“…Prior studies on isolated RNA sequences have pointed toward the possibility that encapsulation and related biophysical effects could increase ribozyme and aptamer activity ( 34 , 35 , 68 ), but the generality of these findings has been unclear. In addition, while compartmentalization is known to be important for the evolution of cooperative phenotypes ( 69 71 ), the evolutionary consequences of RNA encapsulation on noncooperative phenotypes have been largely unstudied, despite being the subject of speculations ( 13 , 72 74 ). Here, we present a systematic study of the effect of encapsulation for five different ribozyme families, previously derived from an exhaustive search of sequence space for self-aminoacylating RNAs, representing three distinct ribozyme motifs and including tens of thousands of different mutant sequences.…”
Section: Discussionmentioning
confidence: 99%